Exploring Sprituality in Grave Pilgrimage: The Case of the Berbah Community at the Kanjeng Panembahan Purboyo Cemetery - Barokah, Fitria Nur; Khoiruddin, Moh (Sunan Kalijaga: International Journal of Islamic Civilization, 2024)
This study explores the religious and cultural significance of pilgrimage practices among the Berbah people at the Kanjeng Panembahan Purboyo Cemetery in Yogyakarta, Indonesia. It aims to examine how pilgrimage practices continue to be observed in contemporary Yogyakarta despite the city's increasing modernization. Limited scholarly attention has been paid to understanding the significance of the continued practice of grave pilgrimage in this country, so this research attempts to capture the lived experiences of local communities using a descriptive qualitative case study approach. The data were collected through participant observations, in-depth interviews, and documentation, allowing for a rich contextual understanding of the phenomenon. This study found that pilgrimage to the cemetery has a deep spiritual meaning for the Berbah people, manifested in three main dimensions: (1) achieving peace of mind through sacred relationships, (2) becoming more aware of human death and impermanence, and (3) clarifying and strengthening one’s purpose in life. These aspects contribute to a higher sense of direction and serenity in the lives of pilgrims, as they believe that pilgrimage invites divine blessings that guide them towards a more meaningful and focused existence.